2004
DOI: 10.3402/ijch.v63i0.17945
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking status among Aboriginal youth

Abstract: These findings demonstrate that Aboriginal youth require different tobacco control strategies compared to non-Aboriginal youth. While these youth experience similar risk factors associated with smoking status, based on the earlier initiation age, tobacco prevention needs to commence much earlier. This study also showcases the positive role that involvement in physical activity plays in building resiliency among Aboriginal youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 6 publications
0
19
1
4
Order By: Relevance
“…In particular, physical activity (11,15), sexual behaviour (16,17) and substance abuse (18) were all equally represented in the Aboriginal youth studies at 33% each, followed by diet [20%] (19) and tobacco use [13%] (4,20). Substance abuse was the most prominent lifestyle factor for the non-Aboriginal youth population, totalling 43% followed by smoking (33%), physical activity (15%), diet (13%) and sexual behaviour (10%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, physical activity (11,15), sexual behaviour (16,17) and substance abuse (18) were all equally represented in the Aboriginal youth studies at 33% each, followed by diet [20%] (19) and tobacco use [13%] (4,20). Substance abuse was the most prominent lifestyle factor for the non-Aboriginal youth population, totalling 43% followed by smoking (33%), physical activity (15%), diet (13%) and sexual behaviour (10%).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cultural appropriateness of care, such as traditional healing, did not appear within any of the studies examining curative services. Furthermore, given the remoteness of a large percentage of Aboriginal youth in terms of residence with 16% living in rural areas and 28% living on-reserve (1), access to such services presents a major concern, yet this issue was examined in only one article (20). …”
Section: Discussionmentioning
confidence: 99%
“…The survey questionnaire, which contains 103 items, was modified and adopted from an established questionnaire used in the GYTS and it was developed by the Child and Adolescent Behaviours in Long‐Term Evolution (CABLE) study 6,17 . This questionnaire was also successfully used in the survey of smoking behaviours for elementary students in Taoyuan, Taiwan 5,12,18 .…”
Section: Methodsmentioning
confidence: 99%
“…Surveys have indicated that the prevalence of tobacco smoking is higher among aboriginal youth compared to non‐aboriginal youth in Australia, Canada, and the United States 6–8 . There is a disparity in smoking behavior between the general and minority populations residing in Taiwanese mountainous areas, especially among the aboriginal population 5,9 .…”
mentioning
confidence: 99%
“…It has been suggested that since there is an earlier age for the initiation of smoking among Native American youth that tobacco prevention efforts should be commenced much earlier than for other groups (Ritchie & Reading, 2004). Nevertheless, research has indicated that prevention approaches found to be effective with White middle-class populations have also been found to be generalizable to other groups, such as to predominantly Hispanic inner-city populations (Botvin, Dusenbury, Baker, James-Ortiz, & Kerner, 1989).…”
Section: Tobacco Use and Ethnicitymentioning
confidence: 99%